A FORMAÇÃO DO PROFESSOR DE LÍNGUA PORTUGUESA: os saberes pedagógicos em foco - Everton, Elizia Graziele Oliveira (2013)
This study analyzes the pedagogical training of Bachelor of Arts of the Federal University of Maranhão, on the campus of Bacanga, headquartered in St. Louis Search to outline the teacher training course from the pedagogical knowledge mobilized in pedagogical subjects. The fabric of this research is based on a qualitative approach, more precisely in the case study, since it addresses a specific case, inserted in the social, economic and political. To do so, use has been made of the semi-structured interview as a methodological tool, with students of the last two periods and teachers pedagogical disciplines. As treatment technique and data analysis, made use of content analysis. Discusses public policies for education and how these affect higher education and, consequently, the training of teachers, models, trends and settings such training course in Literature. Conceptualize themselves teaching knowledge and teaching and reflected on the concepts of language. Finally, we seek to discuss and analyze the pedagogical training in the light of representations of learners and teachers, as well as suggestions that may indicate ways to seek improvements in the teaching-learning pedagogical knowledge. The representations of the subjects of the research show some weaknesses in teacher training, teaching as essentially theoretical, detached from reality and identity with a bachelor's degree. However, it is clear that there is a change perspective, rooted in questions of students and teachers in the daily struggle of pedagogical disciplines belonging to the Department of Arts, so that the course be strengthened as Bachelor and the pedagogical win a prominent place.